Portulaca oleracea L. (Purslane): Protective Properties against Metabolic Syndrome (A review) - Ahmed, Waheeba AlFaki; Alnoumesi, Arjwan Abdullah (Journal of medical and pharmaceutical sciences, 2024)
A complex health disease that is common, metabolic syndrome is caused by a number of interrelated risk factors, such as insulin resistance, obesity, high blood pressure, and dyslipidemia. Dietary plant consumption has drawn interest recently as a possible tactic for managing and preventing the metabolic syndrome. Due to its high nutrient content and possible health advantages, purslane, a succulent plant with a long history of traditional use in a variety of cuisines, has attracted attention. The purpose of this research is to demonstrate how purslane affects metabolic syndrome based on earlier studies. Research indicates that purslane contains a high concentration of bioactive substances with anti-inflammatory and antioxidant qualities, including potassium, flavonoids, and omega-3 fatty acids. These bioactive chemicals from purslane have been shown in multiple studies to effectively lower obesity-related parameters, such as body weight, body mass index (BMI), and fat mass. This helps prevent and treat metabolic syndrome. Consuming purslane has also been linked to improvements in blood pressure, blood glucose, insulin sensitivity, and lipid profile, among other metabolic syndrome components. Purslane extracts have been demonstrated in animal experiments to modulate lipid and glucose metabolism, resulting in a better lipid profile and a reduction in insulin resistance. These results imply that purslane may have a major role in the regulation of metabolic risk variables. In conclusion, given its rich nutritional profile and possible health advantages, purslane consumption offers promise as a dietary strategy for controlling and avoiding the metabolic syndrome.
Keywords: Type 2 Diabetes; Dyslipidemia; Metabolic syndrome; Obesity; Portulaca oleracea